Long COVID and its risk factors in migrants: a nationwide register study from Sweden - Agneta Cederström; George Frederick Mkoma; Thomas Benfield; Charles Agyemang; Marie Nørredam; Mikael Rostila (BMC Medicine)
Abstract Background Many studies have found more severe COVID-19 outcomes in migrants and ethnic minorities throughout the COVID-19 pandemic, while recent evidence also suggests higher risk of longer-term consequences. We studied the risk of a long COVID diagnosis among adult residents in Sweden, dependent on country of birth and accounting for known risk factors for long COVID. Methods We used linked Swedish administrative registers between March 1, 2020 and April 1, 2023, to estimate the risk of a long COVID diagnosis in the adult population that had a confirmed COVID-19 infection. Poisson regressions were used to calculate incidence rate ratios (IRR) of long COVID by country/region of birth. The contribution of sex, preexisting health status, disease severity, vaccination status, and socioeconomic factors to differences in long COVID diagnosis by country/region of birth were further investigated. Results Of the 1,869,188 persons diagnosed with COVID-19 that were included, 7539 had received a long COVID diagnosis. Compared with residents born in Sweden, we found higher risks of long COVID among migrants from East Europe (IRR: 1.44 CI: 1.29–1.60), Finland (IRR: 1.36 CI: 1.15–1.61), South Asia (IRR: 1.28 CI: 1.03–1.59), Other Asia (IRR: 1.35 CI: 1.13–1.62), Other Africa (IRR: 1.48 CI: 1.17–1.87), and the Middle East (IRR: 1.43 CI: 1.27–1.63) in models adjusted for age and sex. We discovered that disease severity, i.e., whether the person was hospitalized (IRR: 18.6 CI: 17.3–20.0) or treated in an intensive care unit (IRR: 120.5 CI: 111.7–129.8), primarily contributed to the higher risk of long COVID found in migrants while the contribution of vaccinations and social conditions were moderate. Preexisting health problems did not contribute to the increased risk of long COVID in migrants. Conclusions The greater exposure and impact of the COVID-19 virus among migrants also affected longer-term consequences. Disease severity was the most important risk factor for long COVID in migrants. The findings emphasize the need for targeted health interventions for migrant communities during an infectious disease pandemic, such as strategic vaccination campaigns and extending social insurance schemes, focusing on reducing disease severity to mitigate the longer-term health consequences of an infection.